Compression of Born ratio for fluorescence molecula tomography/x-ray computed tomography hybrid imaging: Methodology and in vivo validation - Mohajerani, Pouyan; Ntziachristos, Vasilis (Optics Letters, 2013)
The 360° rotation geometryof the hybrid fluorescence molecular tomography/x-ray computed tomography modality allows for acquisition of very large datasets, which pose numerical limitations on the reconstruction. We propose a compression method that takes advantage of the correlation of the Born-normalized signal among sources in spatially formed clusters to reduce the size of system model. The proposed method has been validated using an ex vivo study and an in vivo study of a nude mouse with a subcutaneous 4T1 tumor, with and without inclusion of a priori anatomical information. Compression rates of up to two orders of magnitude with minimum distortion of reconstruction have been demonstrated, resulting in large reduction in weight matrix size and reconstruction time. © 2013 Optical Society of America.
CRIS-Team Scopus Importer:2023-03-08